G47 The development of a paediatric non-cystic fibrosis bronchiectasis service. (24th May 2017) - Peacock, L; Sharp, K; Young, D; Devenny, A
Abstract : Aims: In 2015 the paediatric non CF bronchiectasis clinic underwent service development, including the addition of a dedicated paediatric respiratory nurse and physiotherapist. Routine appointments were expanded to include regular pulmonary function tests and respiratory samples for microbiological culture, which had previously been sent annually. Annual review was introduced. We sought to assess the impact of these changes on patient outcomes. Methods: Patient details were entered into an excel spreadsheet. Information on age, sex, disease and lung function with respect to their best Forced Expiratory Volume in 1 s (FEV1)% predicted in the past year. We included microbiological results and treatment from that year. We compared 2016 data with historical data from 2013. Results: There were a total of 57 patients aged 5 months to 16 years attending the clinic, 24 were males. 17 patients had Primary Ciliary Dyskinesia (PCD), 22 had bronchiectasis and the remainder had recurrent chest infections and chronic wet cough. Their lung function is displayed in the table below. We had lung function results for 13 patients in 2013, they had a mean best FEV1% predicted of 85.85 (SD 13.93). In 2016 the best FEV1 in the patients was higher than in 2013 at 90.23% but the difference is not statistically significant (p=0.348) Respiratory samples were cough swabs, sputum or bronchioalveolar lavage. 26% of patients had positive results. 60% isolated Haemophilus Influenzae . No patients grew Pseudomonas Aeruginosa . Conclusions: Multidisciplinary care is now being provided to these patients, with more detailed assessment being performed. We would require larger patient numbers and more time to demonstrate improvements in lung function.